2020
DOI: 10.1126/sciadv.abb0333
|View full text |Cite
|
Sign up to set email alerts
|

Histone exchange is associated with activator function at transcribed promoters and with repression at histone loci

Abstract: Transcription in eukaryotes correlates with major chromatin changes, including the replacement of old nucleosomal histones by new histones at the promoters of genes. The role of these histone exchange events in transcription remains unclear. In particular, the causal relationship between histone exchange and activator binding, preinitiation complex (PIC) assembly, and/or subsequent transcription remains unclear. Here, we provide evidence that histone exchange at gene promoters is not simply a consequence of PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…Alternatively, it could be hypothesized that the cryptic transcription initiation itself in gene bodies in set2 knockout yeast cells is responsible for the increased histone turnover rate. In support of this, it has recently been found in budding yeast that histone turnover in promoter regions is mediated by transcriptional activators [ 93 , 207 ]. However, because transcriptional activators often directly recruit HATs to promoters, it is difficult to functionally separate transcription initiation from histone acetylation.…”
Section: Function Of Set2/setd2 and H3k36 Methylationmentioning
confidence: 93%
See 1 more Smart Citation
“…Alternatively, it could be hypothesized that the cryptic transcription initiation itself in gene bodies in set2 knockout yeast cells is responsible for the increased histone turnover rate. In support of this, it has recently been found in budding yeast that histone turnover in promoter regions is mediated by transcriptional activators [ 93 , 207 ]. However, because transcriptional activators often directly recruit HATs to promoters, it is difficult to functionally separate transcription initiation from histone acetylation.…”
Section: Function Of Set2/setd2 and H3k36 Methylationmentioning
confidence: 93%
“…However, because transcriptional activators often directly recruit HATs to promoters, it is difficult to functionally separate transcription initiation from histone acetylation. Interestingly, it has also been shown that H3K9 and H3K14, two lysine residues that are often acetylated in active genes, do not affect histone turnover suggesting that histone acetylation does not directly stimulate histone turnover [ 58 , 93 ]. However, it could be argued that many residues on H3 and H4 (as well as H2A/H2B) are acetylated during (cryptic) transcription initiation, all of which might contribute to histone turnover.…”
Section: Function Of Set2/setd2 and H3k36 Methylationmentioning
confidence: 99%
“…For these genes, there was a regularity in the heatmaps pattern revealed ( Figure 15 ), which is possible evidence of AIPL1 involvement in shelterin complex regulation. The role of the shelterin complex, specifically its member RAP1, in global control of histone gene expression was confirmed in several studies [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 81%
“…Since canonical nucleosomes have pseudo two‐fold symmetry, the central nucleosome dyad is considered to be the center of the protected ∼146 bp DNA fragment. However, histone‐DNA interactions are continually disrupted, particularly during transcription, DNA repair, and DNA recombination, where canonical histones can be swapped out with histone variants (Henikoff & Ahmad, 2005; Kassem et al., 2020; Talbert & Henikoff, 2014; Venkatesh & Workman, 2015). Even without full disruption, nucleosomes can transiently unwrap from one or both sides (Li, Levitus, Bustamante, & Widom, 2005).…”
Section: Introductionmentioning
confidence: 99%